If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 215 + (15 + 7) = w Combine like terms: 15 + 7 = 22 215 + (22) = w 215 + 22 = w Combine like terms: 215 + 22 = 237 237 = w Solving 237 = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 237 + -1w = w + -1w Combine like terms: w + -1w = 0 237 + -1w = 0 Add '-237' to each side of the equation. 237 + -237 + -1w = 0 + -237 Combine like terms: 237 + -237 = 0 0 + -1w = 0 + -237 -1w = 0 + -237 Combine like terms: 0 + -237 = -237 -1w = -237 Divide each side by '-1'. w = 237 Simplifying w = 237
| (X-2)(xy+4)=1 | | 3x^2-18x-1056=0 | | 2x-(-14)=100 | | -7b=-9-6b | | 8-j=3 | | (30-3x)=(170-43x) | | -4x+-3=-x+3 | | -9(2x+5)+27=90-9x+72 | | 4(t+2)=n | | 8+2=(16106) | | 3-(4d+9)=21 | | x^3=2kx^2-k^2x | | y^2=4(x+1) | | f(3a)=x-3 | | (-10+1b)+(7b-5)= | | 3+2p=a | | 2x/7-2/7-10/7 | | 48x+48=6(8x+8) | | (s*4)+34=126 | | x/5-7=-10 | | 8m=4(8m+18) | | 8s-(5s+6)=0.2(20+6s) | | -7n+-9=22 | | X+(X*.1)=41.83 | | X^2-3x+60=5x+44 | | 3=3x+4(8) | | X+(X*.08)=41.35 | | 36-5=1 | | 6(2c-13)=138 | | T^2-6t=2t+20 | | 3a-x=42 | | -5/2b-11 |